Criatividades musicais e suas manifestações em um contexto de vulnerabilidade social - Amorim, Quézia Priscila de Barros Silva (2023)
This doctoral thesis stems from a qualitative investigation in the field of Music Education, aiming to comprehend the relationships between musicians' habitus and social representations of music in creative dynamics within a context of social vulnerability. The study utilized the Musical Creativities Workshop (MCW) as a verification instrument, developed through the establishment of bibliographic, epistemological, and methodological bridges, taking into account the specificities of the socioeducational context. These constructions highlight the importance of bridging musical creativity and social vulnerability, grounded in the assumption that democratizing significant and accessible musical experiences for everyone is intrinsically linked to the creative experiences of individuals in learning situations. Drawing on Pierre Bourdieu's field social habitus and Serge Moscovici's social representations, the thesis explores the "why" and "how" within theoretical assumptions and actions in the MCW. The term "musical creativities" (plural), proposed by Pamela Burnard, is adopted to address the multiplicity of creative experiences in music and their diverse manifestations in society. Methodologically, the study adopts a reflexive perspective, integrating techniques relevant to the research subject. In this specific case, it aligns with the socially critical research-action modality, merging it with educational research conducted at the Christian Educational Home (CEH) in the outskirts of Santa Rita – PB, involving children and adolescents aged 8 to 13. The results demonstrate that the comprehensive analysis of musicians' habitus and social representations of music in the specified context served as dispositional centers for musical creativities, expanding reflections on the theme of musical creativity in contexts of social vulnerability and suggesting new directions for future research in the field of music education.